Combining Linked Data and mobiles devices to improve access to OCW - Piedra Pullaguari, N. (2012)
As the Web becomes increasingly populated with diverse data, it continues evolving from a Web of linked documents to a Web Linked Data. This evolution allows relationships to be expressed between content in distributed data sets, enabling the way for integration of raw data from multiple knowledge domains and heterogeneous datasets. However, as the Web becomes increasingly populated with linked data, there is also a need to support users with applications to visualize or to explore available data for a specific task, especially in mobile applications. Examples of these tasks are consuming linked data, or creating new semantic relations between data entities, people and places. With the advent of mobiles, our views and behaviors about access/interaction the Internet are shifting. Specialized applications are available as an important alternative to replace a standard web browser for mobile access. In this article, authors show a three-tier client-server architecture using Android framework. This architecture relies on the RDF data from Linked OpenCourseWare Dataset. Additionally, authors show three proof-of-concept based on architecture which integrates into a common used interface for RDF data management on mobile devices. © 2012 IEEE.